Early mortality of very low-birthweight infants at Queen Elizabeth Central Hospital, Malawi. (1st May 2013) - Rylance, Sarah; Ward, Joseph
Abstract : Background: There is little information regarding outcome of very low-birthweight (VLBW) infants in resource-poor settings. Objectives: To study early mortality outcome in VLBW infants admitted to the neonatal nursery, Queen Elizabeth Central Hospital, Blantyre and determine duration of hospital stay of surviving infants and their attendance for recommended follow-up. Methods: Case notes were reviewed for all infants weighing ≤1500 g at birth admitted to the neonatal unit during a 6-month period (May-October 2010) to establish survival to discharge and follow-up attendance. Results: 42% (112/268) of VLBW infants survived to discharge. Survival significantly increased with increasing birthweight (11% for infants weighing ≤1000 g vs 53% for those >1000 g, P <0·001), and greater gestation (19% for infants <32 weeks vs 68% for ≧32 weeks, P <0·001). Most deaths (88%, 137/156) occurred within the first week, 58% of them (91/156) within 48 hours of admission. Surviving infants with a birthweight of 1001-1500 g stayed in hospital for a mean 21 days (range 5-44) and those weighing ≤1000 g at birth (eight) stayed for a mean 47 days (range 35-64). A total of 108 infants were discharged from hospital, 87 of whom (81%) attended at least one follow-up visit, 62 of whom (57%) completed the recommended follow-up attendance. Conclusion: There is considerable scope to improve survival rates of VLBW infants in this setting, although staffing and economic constraints make survival of the smallest and most premature infants unrealistic. Mothers of surviving infants <1000 g should be prepared for a lengthy hospital stay.